Feedback regulation system for spraying parameters based on online droplet mass deposit measurements - Sun, Chengda; Qiu, Wei (International Journal of Agricultural and Biological Engineering, 2022)
In order to effectively optimize and regulate spraying parameters based on actual spraying performance and improve pesticide utilization rate, in this research, a feedback regulation system for the regulation of spraying parameters was designed based on droplet mass deposit online measurement. The system consisted of an online droplet mass deposit measurement module, wireless transmission module, decision module, and spraying parameters regulation module. First, the droplet mass deposits on the sampling points were measured. Based on the deviation between the measured and expected droplet mass, the expected spraying parameters were determined by the decision module. The spraying parameter was regulated to the expected value by regulating the pulse duty cycle on the pump motor using a micro control unit and a relay. Evaluation tests were conducted indoors using an indoor spraying platform and outdoors using an unmanned aerial vehicle. The results showed that the relative errors between the expected and measured droplet mass deposit after regulation were 6.84% and 11.48% for the indoor and outdoor tests, respectively. Therefore, an optimal spraying performance was observed after regulation. This research provided an experimental platform to quickly optimize spraying parameters and also provided technical references for precision spraying. Keywords: spray, droplet mass deposit, online measurement, wireless transmission, duty cycle, feedback regulation DOI: 10.25165/j.ijabe.20221502.6118 Citation: Sun C D, Qiu W. Feedback regulation system for spraying parameters based on online droplet mass deposit measurements. Int J Agric & Biol Eng, 2022; 15(2): 25–29.